Effect of selective androgen receptor modulator RAD140 on prostate and testosterone levels in Wistar strain rats with bilateral orchidectomy - Budaya, Taufiq Nur; Nurhadi, Pradana; Anita, Kenty Wantri; Nugroho, Prasetyo; Dhani, Fauzan Kurniawan (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Selective androgen receptor modulators (SARMs) have been investigated as a potential treatment for hypogonadism, a condition characterized by low testosterone levels in men. The idea is to provide therapeutic benefits similar to traditional testosterone replacement therapy. However, research in this area is still in its early stages, and more extensive studies are needed to establish the efficacy of SARM. This study aimed to determine the impact of SARM RAD140 on testosterone levels, fibromuscular stroma, and prostate mass in rats undergoing bilateral orchidectomy. METHODS This was an in vivo study using posttest-only control group design in rats (Rattus norvegicus). The positive and negative control groups consisted of rats with and without bilateral orchidectomy, respectively. The treatment groups were rats given SARM RAD140 with and without orchidectomy. Testosterone levels, histopathology, and prostate mass were examined at the end of week 6, and the quantitative data were analyzed using one-way ANOVA. RESULTS This study found no difference in prostate mass (0.598 [0.05] g versus 0.590 [0.07] g, p = 0.984), fibromuscular stroma ratio (0.483 [0.094] versus 0.463 [0.057], p = 0.984), and testosterone level (0.006 [0.005] ng/dl versus 0.014 [0.004] ng/dl, p = 0.098) compared to positive control with orchidectomy and SARM RAD140 administration 6 weeks after treatment. CONCLUSIONS There were no differences in testosterone levels, prostate mass, or the ratio of fibromuscular stroma to epithelium area in rats undergoing bilateral orchidectomy and placebo surgery with the administration of SARM RAD140.